Robotic Repair of a Congenital Isolated Cleft of Anterior Tricuspid Valve Leaflet - Mohanad Hamandi MD; Karim Al-Azizi MD; Alexander Crawford BS; Joy Fan; J. Michael DiMaio MD; Robert L. Smith MD (SAGE Publishing, 2019)
Congenital isolated tricuspid valve (TV) cleft in the anterior leaflet is a rare occurrence, while clefts of the mitral valve leaflets are more common and are usually associated with other congenital heart diseases. In this article, we report a case of TV regurgitation in a young adult female due to an isolated congenital cleft in the anterior TV leaflet, which was surgically repaired using a minimally invasive robotic approach.